Morphology and performance of polyvinyl chloride membrane modified with Pluronic F127 [version 2; referees: 2 approved] - Nasrul Arahman; Afrilia Fahrina; Mukramah Yusuf Wahab; Umi Fathanah (F1000Research, 2018)
Background: Attempts to modify the morphology of membrane for application in industrial separation are being undertaken by many researchers. The present study discusses the morphological modification of polyvinyl chloride (PVC) membrane by combining the hydrophilic surfactant Pluronic F127 (PF127) in a polymer solution to improve the performance of the membrane.  Method: The membrane is formed using the non-solvent induced-phase separation (NIPS) method. PF127 is added to the membrane solution as a membrane modifying agent. The effects of the surfactant concentration in the dope solution on the permeability of pure water, solute rejection, hydrophilic characteristics, and membrane morphology are investigated. Results: Higher concentrations of PF127 had a significant effect on the permeability of pure water. The highest membrane permeation was 45.65 l/m2.hr.atm with the addition of 7% PF127 additive. Conclusion: PF127 is successfully proposed as a membrane pore-forming agent in this work; the blending of this additive in appropriate amounts in the polymer solution is adequate to improve the performance of the PVC membrane.